Rethinking webcomics : webcomics as a screen based medium - Kogel, Dennis (2013)
So far, webcomics, or online comics, have been discussed mostly in terms of ideologies of the Internet such as participatory culture or Open Source. Not much thought, however, has been given to webcomics as a new way of making comics that need to be studied in their own right. In this thesis a diverse set of webcomics such as Questionable Content, A Softer World and FreakAngels is analyzed using a combination of N. Katherine Hayles’ Media Specific Analysis (MSA) and the neo-semiotics of comics by Thierry Groensteen. By contrasting print- and web editions of webcomics, as well as looking at web-only webcomics and their methods for structuring and creating stories, this thesis shows that webcomics use the language of comics but build upon it through the technologies of the Web. Far from more sensationalist claims by scholars such as Scott McCloud about webcomics as the future of the comic as a medium, this thesis shows that webcomics need to be understood as a new form of comics that is both constrained and enhanced by Web technologies. Although this thesis cannot be viewed as a complete analysis of the whole of webcomics, it can be used as a starting point for further research in the field and as a showcase of how more traditional areas of academic research such as comic studies can benefit from theories of digital culture.